Fracture Characteristics and Zoning Model of Overburden during Longwall Mining - Zhengyi Ti; Jiazhen Li; Meng Wang; Xiaoyan Li; Zhupeng Jin; Caiwang Tai; Kang Wang (Shock and Vibration)
The fracture characteristics and zoning model of overburden during longwall mining are the basis of coal mine disaster prevention. However, the existing theoretical model is inconsistent with the field measurement. In order to further research into the strata’s fracture characteristics and optimize the overburden’s zoning model, we used the elasticity and Winkler foundation theory to establish first fracture and periodic fracture mechanics models of clamped boundary supported by an elastic foundation with a key stratum as the research object. We analyzed the stress distribution characteristics and fracture evolution pattern of the mining-induced key stratum. We analyzed the zoning characteristics of mining-induced overburden and established the zoning model according to different fracture mechanisms. The results show that the key stratum formed a double “O-X” shaped interconnected fracture zone after the first fracture. The key stratum formed a double “C-K” shaped interconnected fracture zone after the periodic fracture. We divided the mining-induced overburden into three zones along the horizontal direction: the original rock zone, the inverted triangular compression-shear fracture zone, and the trapezoidal tensile fracture zone. The study revealed the mechanism of inverted step fracture in the separation zone, explained the fracture mechanism of the coal pillar support zone, and has significant theoretical value for the prevention and control of water disasters, gas outbursts, and strata movement.